IMPLEMENTATION OF THE P5 PROJECT EXHIBITION ON TORAJA LOCAL WISDOM IN PRIMARY EDUCATION: - Hakpantria; Mersilina Luther Patintingan; Trivena; Karialviolin Kassa’ Pairunan; Irnes Bulan Dari (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to describe the implementation of an exhibition in the Strengthening Project of Pancasila Student Profile (P5) with the theme of local wisdom at SDN 2 Rantepao and SDN 3 Rantepao. This research employed a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Data analysis in this study used interactive analysis techniques according to Miles and Huberman, namely data reduction, data presentation, and conclusion drawing. The results showed that the planning of activities was carried out collaboratively between teachers and the school team, by adjusting the local cultural content of Toraja into the form of works and performances. The implementation of the project exhibition became a means of student expression in displaying the results of cultural exploration through exhibitions and art performances, which reflected P5 values such as cooperation, diversity, and creativity. Overall, the project exhibition proved to be able to strengthen students’ character and love for local culture through a contextual and meaningful learning process.